Metastases to the nose from clear cell renal cell carcinoma: A case report. Issue 4 (January 2019) - Cui, Pengfei; Cong, Xiaofeng; Yin, Jiaxin; Liu, Miaomiao; Wang, Xinhui; Yang, Lei; Qu, Limei; Liu, Ziling
Abstract: Rationale: Patients with nasal metastases are seldom seen among clear cell renal cell carcinoma (CCRCC). We report a rare case presenting as a solitary nasal cutaneous nodule, and summarize the therapeutic experience of tyrosine kinase inhibitors (TKIs). Patient concerns: A 86-year-old man with a chief complaint of continuous back pain for 3 months and discovery of a cutaneous nodule on the nose for a month visited the oncology department of our hospital. Maxillofacial computed tomography (CT) scans demonstrated a 1.5 × 0.9 cm and ovoid soft tissue density shade at dorsum of the nose. CT of abdomen revealed a 3.5 × 2.7 cm mass in right kidney and presenting an obvious heterogeneous enhancement. Diagnoses: The pathological examination of nasal excision biopsy confirmed the diagnosis of nasal clear cell carcinoma. Immunohistochemical analysis indicated that the nasal metastatic tumor had a renal origin. Interventions: Sunitinib at a dose of 50 mg/day was administered initially, while the serious cutaneous toxicities, especially hand-foot syndrome, occurred to the patient. Subsequently, axitinib at a dose of 5 mg twice daily was accepted as second-line treatment. Outcomes: The nasal mass shrinked significantly after 8-week treatment of axitinib, and the primary tumor has been stable till now. Lessons: Axitinib successfully controlled the nasal cutaneous metastasis with mild adverse reactions, and did not aggravate the cutaneous toxicities resulting from sunitinib. The incidence of cutaneous adverse events were low which had been reported by previous studies; however, it is difficult to say that axitinib is a more effective treatment modality for RCC with nasal metastases, which requires further studies.